2008
DOI: 10.1007/s10495-008-0205-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bovine serum simultaneously stimulates apoptosis and DNA synthesis in premeiotic stages of spermatogenesis in spiny dogfish (Squalus acanthias) in vitro: modulation by androgen and spermatogenic activity status

Abstract: Using the simple cystic spermatogenesis in the shark testis as a model, we previously reported the relative resistance of immature spermatogonia (stem cell and early-stage spermatogonia) to apoptosis in the normal testis and after spermatoxicant exposure in vivo. Apoptosis was monitored by fluorescence image analysis of living cysts, using the validated acridine orange (AO) vital staining technique. Findings show that FBS simultaneously stimulates both apoptosis and [(3)H]thymidine incorporation in immature sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…GDNF treatment decreased apoptosis in a dose-dependent manner, in accordance with its positive effect on mouse SSCs survival through the stimulation of the antiapoptotic factor bcl6b expression [57]. The level of apoptosis in control (without GDNF) was high when compared with apoptosis in the culture of spermatogonial cysts in the spiny dogfish (10-30% in presence of 1% FBS) [58]. In McClusky's experiment, intact cysts were maintained in culture and they probably produced endogenous growth factors which contribute to a moderate apoptosis level [58] whereas in the cultured described here, the presence of somatic supporting cells was drastically limited by an initial differential plating step.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…GDNF treatment decreased apoptosis in a dose-dependent manner, in accordance with its positive effect on mouse SSCs survival through the stimulation of the antiapoptotic factor bcl6b expression [57]. The level of apoptosis in control (without GDNF) was high when compared with apoptosis in the culture of spermatogonial cysts in the spiny dogfish (10-30% in presence of 1% FBS) [58]. In McClusky's experiment, intact cysts were maintained in culture and they probably produced endogenous growth factors which contribute to a moderate apoptosis level [58] whereas in the cultured described here, the presence of somatic supporting cells was drastically limited by an initial differential plating step.…”
Section: Discussionmentioning
confidence: 58%
“…The level of apoptosis in control (without GDNF) was high when compared with apoptosis in the culture of spermatogonial cysts in the spiny dogfish (10-30% in presence of 1% FBS) [58]. In McClusky's experiment, intact cysts were maintained in culture and they probably produced endogenous growth factors which contribute to a moderate apoptosis level [58] whereas in the cultured described here, the presence of somatic supporting cells was drastically limited by an initial differential plating step. In mammals, such high frequency of apoptosis (75%) has been observed in culture of isolated primordial germ cells in absence of feeding cells or growth factors [59].…”
Section: Discussionmentioning
confidence: 68%
“…Cells were differentiated by treating with 100 ng/ml 7 S nerve growth factor for 9 days (Tatton et al, 2002). Cells were washed with RPMI medium containing 1% fetal bovine serum 24 h before experiments and were seeded in 96-and 24-well plates, because fetal bovine serum may influence apoptosis and DNA synthesis (Cui et al, 2004;McClusky, 2008).…”
Section: Cell Culturementioning
confidence: 99%
“…Micromolar concentrations of cadmium caused apoptosis over 2–4 days in culture, and evidence indicated that the elements of the blood‐testis barrier function were negatively influenced (McClusky, 2008 a ). Foetal bovine serum produced both apoptosis and thymidine incorporation in spermatocyst cultures, and the apoptotic effect was decreased by addition of androgen (McClusky, 2008 b ).…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%